Clinical characteristics and long-term management for patients with vitamin D-dependent rickets type II: a retrospective study at a single center in Saudi Arabia - Alsagheir, Afaf; Al-Ashwal, Abdullah; Binladen, Amal; Alhuthil, Raghad; Joueidi, Faisal; Ramzan, Khushnooda; Imtiaz, Faiqa (Frontiers in Endocrinology, 2024)
Introduction: Hereditary Vitamin D-dependent rickets type II (HVDDR-type II) is a rare autosomal recessive disorder caused by molecular variation in the gene encoding the vitamin D receptor (VDR). This study aims to evaluate phenotype and genotype characteristics and long-term follow-up of the largest group of patients with (HVDDR-type II) in Saudi Arabia. Methodology: We conducted a retrospective chart review to collect the clinical, biochemical, and genetic data for all HVDDR-type II patients currently receiving treatment at King Faisal Specialist Hospital & Research Centre, Riyadh, Saudi Arabia. Results: A total of 42 patients, 57.1% female, and 42.9% male were included in the study. Seven patients were treated with high doses of oral calcium, while 35 patients were treated with IV calcium infusion. The median age at presentation was 15.5 months. Alopecia was found in 97.6%, 21.4% presented with bowing legs, 14.3% with delayed walking, 9.5% with seizure, and 2.4% presented with respiratory failure, while a family history of the disease was positive in 71.4% of total patients. Molecular genetic testing of the VDR gene in our cohort identified six different gene variants c.885 C>A (p.Tyr295Ter), c.88 C>T (p.Arg30Ter), c.1036G>A (p.Val346Met), c.820C>T (p.Arg274Cys), c.803 T>C (p.Ile268Thr), and c.2T>G (p.Met1?). Conclusion: We are describing the largest cohort of patients with HVDDR-type II, their clinical biochemical findings, and the most prevalent genetic variants in our population.